EXAMINING THE RELATIONSHIP AMONG BELIEFS, PEDAGOGICAL-MATHEMATICAL KNOWLEDGE, AND EARLY NUMERACY INSTRUCTION IN PRE-SERVICE TEACHERS: AN EXPLORATORY SEQUENTIAL MIXED-METHODS STUDY - Widayati, Sri; Siswono, Tatag Eko Yuli; Wiryanto, Wiryanto; Mariana, neni; Wahyuni, Molli; Ekawati,, Rooselyna (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
Early numeracy provides a foundation for later mathematical learning, yet early instruction often falls short of developmental expectations. This exploratory sequential mixed-methods study examined how pre-service early childhood teachers' belief orientations and pedagogical-mathematical knowledge jointly relate to instructional practice in early numeracy. In Phase I, six pre-service teachers were purposively selected and studied through interviews, lesson-plan analysis, and teaching observation. Cross-case thematic analysis identified three dominant belief orientations, namely instrumentalist, Platonist, and problem-solving, together with hybrid profiles that revealed uneven links between symbolic and contextual approaches. In Phase II, 182 pre-service teachers from three public universities in East Java completed an expert-reviewed and empirically screened 90-item questionnaire measuring belief orientation, pedagogical-mathematical knowledge, and self-reported instructional practice. The integrated regression model explained 73.4% of the variance in instructional practice (R2 = 0.734, p < .001). Both belief orientation (β = 0.328, p < .001) and pedagogical-mathematical knowledge (β = 0.568, p < .001) significantly predicted practice, with pedagogical-mathematical knowledge emerging as the stronger predictor. The integrated findings suggest that beliefs shape pedagogical direction, whereas pedagogical-mathematical knowledge determines how effectively that direction can be enacted. The study contributes to the literature by showing that the belief-practice relationship in early numeracy is best understood as an enactment issue: beliefs orient teaching, but knowledge enables meaningful classroom implementation. The findings imply that teacher education should move beyond efforts to reshape beliefs alone and invest more systematically in topic-specific pedagogical knowledge of number concepts, representations, misconceptions, and scaffolding